1990
DOI: 10.1002/j.2333-8504.1990.tb01365.x
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Use of Simplified Irt Models for Scaling and Equating the Toefl Test

Abstract: A continuing program of research related to the TOEFL test is carried out under the direction of the TOEFL Research Committee. Its six members include representatives of the Policy Council. the TOEFL Committee of Examiners, and distinguished English as a second language specialists from the academic community. Currently the Committee meets twice yearly to review and approve proposals for test-related research and to set guidelines for the entire scope of the TOEFL research program. Members of the Research Comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
1
7
1
Order By: Relevance
“…But a previous TOEFL research study using the modified Rasch model was conducted by Hicks (1984) and another by Way and Reese (1991). Both of these studies compared the performance of this modified Rasch model with 3PL; and both found in favor of 3PL, in contrast with the present study.…”
contrasting
confidence: 72%
See 1 more Smart Citation
“…But a previous TOEFL research study using the modified Rasch model was conducted by Hicks (1984) and another by Way and Reese (1991). Both of these studies compared the performance of this modified Rasch model with 3PL; and both found in favor of 3PL, in contrast with the present study.…”
contrasting
confidence: 72%
“…The study by Way and Reese (1991) was a simulation study in which 3PL was used to generate simulated samples, and then the fit of other models to those samples was evaluated. In such a situation the 3PL model should be the favorite because it is approximating itself.…”
mentioning
confidence: 99%
“…It was assumed that enough similarities exist between the three sections of the TOEFL that results based on one of the sections would be relevant for the other two sections. Support for this assumption can be seen in the simulation results reported by Way and Reese (1991). The structure of the data for Simulation I was identical to the structure of the operational TOEFL data that were analyzed in the real data portion of the study.…”
Section: Datasupporting
confidence: 58%
“…However, in estimating the true score equating relationship, which is a common application at ETS, the two programs were about equally accurate when the number of items in a test was greater than or equal to 20. In a simulation study based on the TOEFL operational equating design, Way and Reese (1991) found that although correlations between LOGIST 3PL item parameter estimates and generating "true" parameters tended to be affected by sample size, neither the quality of model-data fit nor the quality of simulated equatings appeared to be sensitive to sample size. In their study, sample sizes for equating set items ranged from 600 to 1,500, while operational items were based on sample sizes ranging from 2,400 to 6,000.…”
Section: Number Of Examinees (N)mentioning
confidence: 99%
See 1 more Smart Citation